Casa nova, vida nova? Mobilidade urbana nos empreendimentos minha casa minha vida (faixa 1) na região metropolitana de Natal - Rodrigues, Diana Araújo (2018)
The term urban mobility was used initially as a synonym of urban transport, only later the expression urban mobility began to be used to define something more comprehensive, raising the need to incorporate other aspects in the ordering of the offsets in the cities, going beyond the transport system plan. The term accessibility is often confused with mobility, and that addition of expressions to refer to everyday offsets indicates a paradigm shift, highlighting the targeting of the focus of urban mobility planning for people rather than for vehicles. It was introduced as well the need to add the idea of sustainability planning, and support, through the mobility planning, inequalities and social inclusion. The most current research on transport and mobility reveal the progressive construction of a deeper reflection from the point of view of the aspects and social impacts of urban mobility, which favored the emergence of new perspectives to propose more efficient practices in planning of governmental actions, which do not only restrict to the remedy of traffic problems, and that could interfere in the framework of sociospatial segregation, increasing access to opportunities for low-income layers. Research indicates that in the "Programa Minha Casa Minha Vida (faixa 1)" housing production, in RMNatal, there are problems with the communities' locations. The premise found in these researches is that the enterprises are inserted in outlying areas devoid of services and necessary equipment to the everyday life, which would configure a framework of socialspatial segregation. That previous finding in the consulted researches motivated the choice of the empiric study in this field. The objective of this research is to accomplish a more specific and wide analysis of the enterprises of this program (in RMNatal) referring to the conditions of urban mobility, supplanting the diagnoses already designed about the urban insertion of the groups, seeking to understand in what way those locations constitute a segregation framework in fact, which reflection that has for the residents' insertion in the opportunities structures, and in what way the mobility could interfere positively.